Observation of free surface flow behavior using laser tagging method by photochromic dye tracer - Nurrina, Rosli (2015)
Free surface flows are ubiquitous in our daily life. For instances, the river flow, sea wave, rain droplet, water column flow out from a water tap and water flow in a drain are among the examples of free surface flow that commonly found in our everyday life. Moreover, the free surface flow is also observed in many branches of the industrial fields including the atomization process in automotive engine, wall surface flow related to heat and mass transfer facilities as well as the wave surface flow related two phase flow in thermal exchanger.